(3TQM GdQSGdI GdHgGFjI aj GdMSGHs - (3GdeQYTj, YHO GdQMje Hf CHj HcQ Hf SdjeGf, J(B1068(3g`s
(3ChdgG (B:s
(3fMeOc jG ef dG jLeY LPhQ CbSGeg GdCagGeCeG HYO ajbhdYHO GdQMje Hf CHj HcQ Hf SdjeGf GdeQYTj deG cGf Yde GdMSGH ef CLd GdYdhehcGfJ GdQSGdI GdHgGFjI ef QSGFdg hCQOJ Cf CHfj GdeSGeMGJs
(3BNQgG (B:s
(3aGdQeM eLehYI GKfi YTQ PQGYG hfUa PQGY hgh GdeWdhH hdGSJNQGL gPg GdeSCdI hfXGFQgG WQb CNQ JWdH eY HQGgjfgG ef cJGHfG GdcHjQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: 2 / 129s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdQjGVjGJs